Powder coating with good high-temperature resistance, high-temperature-resistant coating and preparation method

Through the coordinated design of multi-layer coating structure and components, the problem of thermal conductivity and thermal insulation coordination of coating in extreme environments is solved, and the efficient thermal conductivity, thermal insulation, wear resistance and corrosion resistance of coating is achieved. It is suitable for high-end fields such as aerospace, nuclear power, and new energy vehicles.

CN120535984AActive Publication Date: 2025-08-26GUANGDONG YINDA TECH CO LTD

Patent Information

Application Number
CN202510649605.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-08-26
Estimated Expiration
2045-05-20

AI Technical Summary

Technical Problem

The existing coating technology is difficult to achieve the coordination between axial heat conduction and radial heat insulation in the same coating, and cannot simultaneously improve high temperature resistance, corrosion resistance and mechanical properties.

Method used

The multi-layer coating structure is adopted, including base coating, intermediate coating and top coating. The boron nitride sheet is arranged in a directional manner through a magnetic field to form a thermal conductivity channel. Combining nanokaolinite/talc powder composites, Zr-Ti-V composite oxides and silica aerogels and other components, a thermal insulation network is formed to improve the high temperature, corrosion resistance and mechanical properties of the coating.

Benefits of technology

It realizes the efficient thermal conductivity, heat insulation, wear resistance, thermal shock resistance and corrosion resistance of the coating, significantly improves the high temperature resistance and service life of the coating, and is suitable for material protection in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535984A_ABST
    Figure CN120535984A_ABST
Patent Text Reader

Abstract

The invention provides a powder coating with good high-temperature resistance, a high-temperature-resistant coating and a preparation method, and belongs to the field of high-temperature-resistant coatings. The powder coating is composed of a prime coating, a middle coating and a surface coating, the prime paint is prepared from the following chemical components: 20 to 40 parts of organic silicon-epoxy-polyarylether sulfone ternary hybrid resin, 5 to 15 parts of boron nitride, 2 to 6 parts of KH-550 modified silicon carbide and 3 to 8 parts of Al2O3 coated SiO2 core-shell particles; the middle-layer coating is prepared from the following chemical components: 10 to 20 parts of polyimide-siloxane hyperbranched resin, 3 to 6 parts of Zr-Ti-V composite oxide and 1 to 4 parts of nano kaolinite / talcum powder compound; the surface layer coating is prepared from the following chemical components: 10 to 20 parts of organic silicon-epoxy-polyarylether sulfone ternary hybrid resin, 5 to 15 parts of silicon dioxide aerogel and 1 to 3 parts of ammonium polyphosphate / zinc borate compound. Therefore, the high-temperature resistance, the corrosion resistance and the mechanical property of the high-temperature-resistant coating are improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of high-temperature resistant coatings, and in particular to a powder coating with excellent high-temperature resistance, a high-temperature resistant coating, and a preparation method. Background Art

[0002] High-temperature resistant coatings are a core protective technology for extreme high-temperature environments in aerospace, energy and power, chemical equipment, and other applications. Their core functions include resisting high-temperature oxidation and corrosion, blocking heat transfer, and maintaining the mechanical properties of the substrate.

[0003] As industrial equipment develops towards high power density and lightweight, traditional coating technology faces the following bottlenecks: ceramic-based coatings (such as Al2O3, ZrO2), although they have excellent temperature resistance (>1000℃), are brittle (fracture toughness <2MPa·m 1 / 2 ), poor thermal shock resistance (number of cycles < 5 times), and high thermal conductivity (> 20W / m·K), which cannot prevent heat from being transferred to the substrate; silicone resin coatings are flexible and easy to construct, but have a low upper temperature limit (usually < 300°C), are prone to decomposition and weight loss at high temperatures (> 10%), and lack directional thermal management capabilities. The components of the composite coating are not synergistic enough, and traditional solutions make it difficult to achieve synergy between axial heat conduction (heat dissipation) and radial thermal insulation (protection) in the same coating. High-rigidity resins (such as epoxy resins) are prone to brittle cracking at high temperatures, while flexible resins (such as silicone rubber) are difficult to support the filler network, resulting in the coating being easily peeled off under thermal-mechanical coupling. Therefore, how to simultaneously improve the high-temperature resistance, corrosion resistance, and mechanical properties of high-temperature resistant coatings is a technical problem that urgently needs to be solved. Summary of the Invention

[0004] The present application provides a powder coating with excellent high-temperature resistance, a high-temperature resistant coating and a preparation method to solve the following technical problem: how to simultaneously improve the high-temperature resistance, corrosion resistance and mechanical properties of the high-temperature resistant coating.

[0005] In a first aspect, the present application provides a powder coating with excellent high temperature resistance, wherein the powder coating comprises a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0006] The primer is composed of the following chemical components: 20-40 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of boron nitride, 2-6 parts of KH-550 modified silicon carbide, and 3-8 parts of Al2O3@SiO2 core-shell particles;

[0007] The intermediate layer coating is composed of the following chemical components: 10-20 parts of polyimide-siloxane hyperbranched resin, 3-6 parts of Zr-Ti-V composite oxide, and 1-4 parts of nano-kaolinite / talc powder mixture;

[0008] The surface coating consists of the following chemical components: 10-20 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of silicon dioxide aerogel, and 1-3 parts of ammonium polyphosphate / zinc borate compound.

[0009] Optionally, in the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 1:1 to 3:1;

[0010] In the ammonium polyphosphate / zinc borate compound, the mass ratio of ammonium polyphosphate to zinc borate is 2:1 to 3:1;

[0011] The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm.

[0012] Optionally, the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials, in parts by mass: 50-65 parts of polymethylphenylsiloxane, 20-30 parts of bisphenol A epoxy resin, and 10-20 parts of fluorine-terminated polyarylethersulfone;

[0013] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 50 to 80 parts of polyimide prepolymer, 12 to 20 parts of benzocyclobutene crosslinking agent, 20 to 35 parts of hydroxyl-terminated polydimethylsiloxane, and 5 to 15 parts of vinyl siloxane side chains.

[0014] In a second aspect, the present application provides a method for preparing a powder coating having excellent high temperature resistance according to any one of the first aspects, the method comprising:

[0015] Mixing organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, boron nitride, KH-550 modified silicon carbide and Al2O3@SiO2 core-shell particles to obtain the primer;

[0016] Mixing a polyimide-siloxane hyperbranched resin, a Zr-Ti-V composite oxide, and a nano-kaolinite / talc powder mixture to obtain the intermediate layer coating;

[0017] The surface coating is obtained by mixing a ternary hybrid resin of organosilicon-epoxy-polyarylethersulfone, a silica aerogel and an ammonium polyphosphate / zinc borate compound.

[0018] Optionally, the preparation method of the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin includes:

[0019] Adding polymethylphenylsiloxane, bisphenol A epoxy resin and fluorine-terminated polyarylethersulfone to an organic solvent in proportion to obtain a first mixed solution;

[0020] Adjusting the pH value of the first mixed solution to 3-4 and performing a stirring reaction to form a sol-gel interpenetrating network to obtain a second mixed solution;

[0021] A titanate catalyst was added to the second mixed liquid, and the temperature was raised to 120° C. for reaction for 2 hours to obtain the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin.

[0022] Optionally, the preparation method of the polyimide-siloxane hyperbranched resin includes:

[0023] adding a polyimide prepolymer, a hydroxyl-terminated polydimethylsiloxane, and a titanate catalyst into an organic solvent to carry out a condensation reaction at 120° C. for 8 hours to obtain a third mixed solution;

[0024] Adding vinyl siloxane side chains to the third mixed solution and reacting at 80° C. for 4 hours to hydrolyze and condense the siloxane to form branching points, thereby obtaining a fourth mixed solution;

[0025] Adding a benzocyclobutene crosslinker and a free radical initiator to the fourth mixed solution, then heating to 140° C. and reacting for 6 hours under nitrogen protection to open the ring structure of the benzocyclobutene crosslinker and crosslink the vinylsiloxane side chains, to obtain a fifth mixed solution;

[0026] The fifth mixed liquid is post-processed and purified to obtain the polyimide-siloxane hyperbranched resin.

[0027] Optionally, the preparation method of the Zr-Ti-V oxide includes:

[0028] The zirconium nitrate solution, tetrabutyl titanate solution and ammonium metavanadate solution are mixed, and ammonia water is slowly added dropwise to adjust the pH value to 8.8-9.2 to perform a coprecipitation reaction to form a precipitate; the coprecipitation reaction temperature is room temperature and the time is 12-24 hours;

[0029] calcining the precipitate to obtain a Zr-Ti-V composite oxide sintered block; the calcination temperature is 1100-1300° C., and the time is 3-5 hours;

[0030] The Zr-Ti-V composite oxide sintered block is subjected to high-energy ball milling to obtain the Zr-Ti-V oxide.

[0031] Optionally, the preparation method of the Al2O3@SiO2 core-shell particles includes:

[0032] The hydroxylated Al2O3 was dispersed in KH-550 ethanol solution and stirred at 60°C for 4 hours to allow the silane to bond to the Al2O3 surface to obtain modified Al2O3;

[0033] Adding ethyl orthosilicate to an ethanol / water mixed solution of modified Al2O3, and slowly adding ammonia water to adjust the pH value to 9-10, then stirring at a constant temperature of 50°C for 6 hours to allow the ethyl orthosilicate to hydrolyze to generate SiO2 and deposit on the Al2O3 surface, and centrifuging to obtain a coating;

[0034] The coating is calcined at high temperature to obtain the Al2O3@SiO2 core-shell particles; the temperature of the high temperature calcination is 550-650°C and the time is 1.5-2.5h.

[0035] In the third aspect, the present application provides a high-temperature resistant coating, which is formed by spraying and curing the powder coating with good high-temperature resistance described in any one of the first aspects. In the high-temperature resistant coating, the boron nitride is oriented along the direction of heat flow through the magnetic field, and forms an anisotropic thermal conductive-insulating network with the silica aerogel.

[0036] In a fourth aspect, the present application provides a method for preparing the high-temperature resistant coating according to the third aspect, the method comprising:

[0037] The primer is sprayed onto the surface of the substrate, and a transverse magnetic field is applied parallel to the substrate surface to orient the boron nitride flakes along the direction of heat flow to form a bottom layer;

[0038] Spraying the intermediate layer coating onto the surface of the bottom layer to form an intermediate layer;

[0039] The surface coating is vertically sprayed onto the surface of the intermediate layer to form an axial heat conduction-radial heat insulation network, and then cured to obtain the high-temperature resistant coating.

[0040] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0041] The present application provides a powder coating with excellent high-temperature resistance. The powder coating consists of a base coating, an intermediate coating and a top coating. The composition of each layer of coating is rationally designed, thereby simultaneously improving the high-temperature resistance, corrosion resistance and mechanical properties of the high-temperature resistant coating.

[0042] First, the base coating is a thermally conductive and wear-resistant layer. Boron nitride (BN) flakes are oriented in a magnetic field, forming a heat conduction channel along the direction of heat flow (parallel to the substrate surface), quickly dissipating localized high-temperature heat (such as the leading edge of an engine blade). Simultaneously, KH-550 modified silicon carbide (SiC) with a hardness of 9.5 on the Mohs scale is combined with Al2O3@SiO2 core-shell particles (the Al2O3 core enhances rigidity, while the SiO2 shell buffers stress), improving wear life. Furthermore, the core-shell particles absorb thermal stress through plastic deformation, improving resistance to thermal shock cycles.

[0043] Secondly, the intermediate layer coating is a transition buffer layer, and the nano-kaolinite / talc powder compound alleviates the thermal expansion mismatch stress through sheet slippage, thereby improving the adhesion retention rate after thermal cycling. At the same time, the Zr-Ti-V composite oxide forms ZrTiO4-VO x Solid solution, inhibiting thermal oxidation of the resin. In addition, the hyperbranched resin chemically bonds with the bottom layer / surface layer through the terminal functional groups (amino / epoxy), improving the interlayer bonding strength.

[0044] Finally, the topcoat acts as a thermal insulation and flame retardant layer. Silica aerogel is deposited onto the surface through a vertical spraying process, creating a radially distributed gradient insulation barrier that significantly reduces heat transfer through the thickness (radial direction). A combination of ammonium polyphosphate (APP) and zinc borate (ZB) provides highly effective flame retardancy. The thioether bonds in the ternary hybrid resin inhibit acid and alkali corrosion, improving chemical resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0046] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0047] Figure 1 A schematic flow chart of a method for preparing a powder coating with excellent high-temperature resistance provided in an embodiment of the present application. DETAILED DESCRIPTION

[0048] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0049] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0050] In a first aspect, the present application provides a powder coating with excellent high temperature resistance, wherein the powder coating comprises a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0051] The primer is composed of the following chemical components: 20-40 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of boron nitride, 2-6 parts of KH-550 modified silicon carbide, and 3-8 parts of Al2O3@SiO2 core-shell particles;

[0052] The intermediate layer coating is composed of the following chemical components: 10-20 parts of polyimide-siloxane hyperbranched resin, 3-6 parts of Zr-Ti-V composite oxide, and 1-4 parts of nano-kaolinite / talc powder mixture;

[0053] The surface coating consists of the following chemical components: 10-20 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of silicon dioxide aerogel, and 1-3 parts of ammonium polyphosphate / zinc borate compound.

[0054] The powder coating in this application consists of a base coating, an intermediate coating and a top coating. The functions of each layer are as follows:

[0055] The base coating is a thermally conductive, wear-resistant layer. Boron nitride (BN) flakes are aligned in a magnetic field, forming heat conduction channels along the direction of heat flow (parallel to the substrate surface), rapidly dissipating localized high-temperature heat (such as at the leading edge of an engine blade). KH-550 modified silicon carbide (SiC), with a hardness of 9.5 on the Mohs scale, is combined with Al2O3@SiO2 core-shell particles (the Al2O3 core enhances rigidity, while the SiO2 shell buffers stress), extending wear life. Furthermore, the core-shell particles absorb thermal stress through plastic deformation, improving resistance to thermal shock cycles.

[0056] The intermediate layer of coating is a transition buffer layer. The nano-kaolinite / talc powder compound relieves the thermal expansion mismatch stress through sheet slippage, thereby improving the adhesion retention rate after thermal cycling. At the same time, Zr-Ti-V composite oxide forms ZrTiO4-VO x Solid solution, inhibiting thermal oxidation of the resin. In addition, the hyperbranched resin chemically bonds with the bottom layer / surface layer through the terminal functional groups (amino / epoxy), improving the interlayer bonding strength.

[0057] The topcoat acts as a thermal insulation and flame retardant layer. Silica aerogel is deposited onto the surface through a vertical spraying process, creating a radially distributed gradient insulation barrier that significantly reduces heat transfer through the thickness (radial direction). The ammonium polyphosphate (APP) / zinc borate (ZB) compound provides highly effective flame retardancy. The thioether bonds in the ternary hybrid resin inhibit acid and alkali corrosion, improving chemical resistance.

[0058] After the basecoat, intermediate coating, and topcoat are sprayed and cured to form a coating, although the basecoat, intermediate coating, and topcoat are independent layers, there is a certain degree of component penetration and interaction in the interface area. Specifically, the functions and interactions of the various components of the powder coating with excellent high-temperature resistance provided by this application are as follows:

[0059] Silicone-epoxy-polyarylethersulfone ternary hybrid resin: The silicone component provides the flexibility and high-temperature resistance of the main chain. The Si-O bond has high bond energy and remains stable below 400°C to prevent thermal decomposition. The epoxy resin forms a three-dimensional network through epoxy group cross-linking, giving the coating high adhesion and impact resistance; after curing, it forms a rigid skeleton to inhibit high-temperature creep. The aromatic ring structure of polyarylethersulfone (PAES) provides excellent thermal stability and resistance to thermal oxidation, and the sulfide bond enhances chemical corrosion resistance. The three form an interpenetrating network (IPN) through the sol-gel method. The silicone disperses the rigid areas of PAES, and the epoxy resin fills the interfacial gaps, making the coating both flexible and rigid in the range of -50 to 400°C and reducing the thermal expansion coefficient.

[0060] Boron Nitride: Hexagonal BN crystals (h-BN) are oriented along the (002) crystal plane, with an in-plane thermal conductivity of up to 300 W / (m·K), creating a rapid axial heat dissipation channel. At the same time, their high volume resistivity prevents leakage or arc damage at high temperatures. Furthermore, the layered structure reduces friction and improves the wear resistance of the coating. Magnetic field orientation technology aligns the BN layers parallel to the coating surface, resulting in an axial thermal conductivity greater than 50 W / (m·K). This creates a "thermal diode" effect with the radial insulation filler (silica aerogel), reducing the temperature rise of the substrate.

[0061] KH-550 modified silicon carbide: The amino groups of KH-550 react with the surface hydroxyl groups of silicon carbide (SiC), forming -Si-O-Si- bonds. This improves compatibility with the resin and enhances interfacial shear strength. The SiC, with its Mohs hardness of 9.5, enhances the wear resistance of the coating when combined with the resin. The SiC and Al2O3@SiO2 core-shell particles form a "hard-soft" composite structure, with the SiC bearing the primary wear stress while the core-shell particles cushion impact, extending the coating's life.

[0062] Al2O3@SiO2 core-shell particles: The Al2O3 core (50-100nm) provides high modulus, while the SiO2 shell (10-30nm) absorbs thermal stress through plastic deformation, achieving thermal shock resistance exceeding 50 cycles. Furthermore, the SiO2 shell protects against acidic and alkaline media, enhancing salt spray resistance. The core-shell particles and Zr-Ti-V oxides work together to inhibit interfacial crack propagation and improve the coating's fracture toughness.

[0063] Polyimide-siloxane hyperbranched resin: The aromatic heterocyclic structure of the polyimide (PI) main chain provides extreme temperature resistance, and the rigid chain segments inhibit the sliding of the molecular chain at high temperatures. The siloxane side chains enhance flexibility through the Si-O-Si segments grafted by KH-550, reduce the brittleness of the coating, and increase the elongation at break. The multi-terminal functional groups (such as amino and epoxy groups) of the hyperbranched structure enhance the chemical bonding with the ternary hybrid resin, forming a dense cross-linked network and reducing microcracks. As a "molecular enhancer", the hyperbranched resin decomposes the siloxane side chains at high temperatures (>300°C) to absorb heat, delaying the thermal degradation of the matrix, while the PI main chain maintains the structural integrity.

[0064] Nano-kaolinite / talc powder compound: kaolinite Al2Si2O 5( OH)4 and talc Mg3Si4O 10 Nanosheets of (OH)2 are interspersed within the resin, enhancing hardness and scratch resistance. Furthermore, the parallel arrangement of the sheets extends the gas diffusion path, increasing the oxygen index. The interlayer slippage of talc alleviates thermal stress, complementing the rigidity of kaolinite, ensuring that the coating maintains over 95% adhesion after thermal cycling (-196°C to 600°C).

[0065] Zr-Ti-V composite oxide: ZrO2 provides high temperature phase transformation toughening effect (tetragonal phase → monoclinic phase), TiO2 enhances interface bonding, V2O5 inhibits the coarsening of precipitate phase by forming low mobility grain boundary segregation layer, and the multi-element synergy of composite oxide can form metastable phase, delaying the aggregation of precipitate phase at high temperature. x It forms a solid solution, has no phase change below 1200℃, and its thermal expansion coefficient matches the substrate, preventing the coating from cracking. 4+ / V 5+ The redox couple absorbs free radicals, slowing down the thermal oxidation of the resin. Zr-Ti-V oxide reacts with ammonium polyphosphate to form a ZrP2O7-TiP2O7 glass phase, which covers the surface of the carbon layer and improves flame retardancy.

[0066] Silica aerogel: This suppresses gas molecular heat conduction through the Knudsen effect, reducing radial thermal conductivity. Vertical spraying forms a gradient insulation layer that, in conjunction with the axial heat conduction of BN, allows the temperature difference between the coating surface (high-temperature side) and the substrate (low-temperature side) to reach 500°C.

[0067] Ammonium polyphosphate / zinc borate combination: Ammonium polyphosphate (APP) decomposes at 250-400°C to form polyphosphoric acid, which catalyzes the dehydration of the resin into char, forming an expanded char layer that blocks oxygen and heat. Zinc borate (ZB) forms a B2O3 glass layer above 350°C, covering the char layer and suppressing smoke and dripping. The APP / ZB combination produces significantly better char residue after combustion than a single flame retardant alone.

[0068] This formula achieves high temperature resistance and intelligent thermal management through multi-scale filler design, functional additive coupling, and interface synergistic optimization. Its comprehensive performance significantly exceeds that of a single component system. The synergistic effects between the components are as follows:

[0069] (1) Thermal management synergy: The thermal conductivity and insulation network of boron nitride (axial) + aerogel (radial) is integrated. The BN is arranged in a directional manner to form an axial fast heat conduction path to guide local hot spots. Aerogel is sprayed vertically to construct a radial insulation barrier to reduce the overall heat flux.

[0070] (2) Synergistic mechanical properties: The rigid-flexible composite structure of ternary hybrid resin (rigid) + hyperbranched resin (flexible), the rigid resin provides high strength, and the hyperbranched structure absorbs stress through molecular chain entanglement to prevent brittle fracture.

[0071] (3) Synergistic high-temperature stability: The multi-scale fillers of Zr-Ti-V oxide (nanoscale) + Al2O3@SiO2 (core-shell) complement each other. Zr-Ti-V bimodal particles fill the micropores and inhibit the decomposition of the resin at high temperature. Al2O3@SiO2 buffers the thermal stress and prevents interface peeling.

[0072] (4) Interface enhancement synergy: Surface modification and gradient dispersion of KH-550 modified silicon carbide + nano-kaolinite / talc powder, silane coupling agent enhances the interface bonding between silicon carbide and resin; dense filling of kaolinite / talc powder reduces stress concentration.

[0073] In some embodiments, in the nano-kaolinite / talc mixture, the mass ratio of nano-kaolinite to talc is 1:1 to 3:1;

[0074] In the ammonium polyphosphate / zinc borate compound, the mass ratio of ammonium polyphosphate to zinc borate is 2:1 to 3:1.

[0075] In some embodiments, the Zr-Ti-V composite oxide is a bimodal nanoparticle consisting of large particles of 50 to 100 nm and small particles of 5 to 20 nm.

[0076] It should be noted that the large-sized precipitates of 50nm to 100nm mainly pin the grain boundaries and inhibit grain coarsening at high temperatures; the small-sized precipitates of 5nm to 20nm restrict dislocation movement through the dislocation pinning effect and improve the high-temperature creep resistance of the coating.

[0077] In some embodiments, the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials, in parts by mass: 50 to 65 parts of polymethylphenylsiloxane, 20 to 30 parts of bisphenol A epoxy resin, and 10 to 20 parts of fluorine-terminated polyarylethersulfone;

[0078] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 50 to 80 parts of polyimide prepolymer, 12 to 20 parts of benzocyclobutene crosslinking agent, 20 to 35 parts of hydroxyl-terminated polydimethylsiloxane, and 5 to 15 parts of vinyl siloxane side chains.

[0079] Figure 1 A schematic flow chart of a method for preparing a powder coating with excellent high-temperature resistance provided in an embodiment of the present application.

[0080] Second, as Figure 1 As shown, the present application provides a method for preparing a powder coating with good high temperature resistance as described in any one of the first aspects, the method comprising:

[0081] S1, mixing a silicone-epoxy-polyarylethersulfone ternary hybrid resin, boron nitride, KH-550 modified silicon carbide and Al2O3@SiO2 core-shell particles to obtain the primer;

[0082] It should be noted that the specific steps of step S1 are as follows: placing the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin in a mixing container and heating it to 60-80°C to soften it and increase its fluidity. Adding boron nitride powder to the resin and mixing it using a high-speed disperser or ball mill to ensure that the boron nitride is evenly dispersed in the resin. Add KH-550 modified silicon carbide and continue mixing to ensure that the silicon carbide particles are fully in contact with and coated by the resin. Finally, add Al2O3@SiO2 core-shell particles and stir at a low speed to avoid destroying the core-shell structure while ensuring that the particles are evenly distributed.

[0083] In some embodiments, the preparation method of the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin includes:

[0084] Polymethylphenylsiloxane, bisphenol A epoxy resin and fluorine-terminated polyarylethersulfone are added to an organic solvent in proportion to obtain a first mixed solution; the pH value of the first mixed solution is adjusted to 3-4, and the mixture is stirred to react to form a sol-gel interpenetrating network to obtain a second mixed solution; a titanate catalyst is added to the second mixed solution, and the mixture is heated to 120°C and reacted for 2 hours to obtain the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin; the mass of the titanate catalyst is 0.5-1.5% of the mass of the second mixed solution.

[0085] During the preparation of organosilicon-epoxy-polyarylethersulfone ternary hybrid resins, adjusting the pH to 3-4 promotes the ring-opening reaction between silanol (Si-OH) and epoxy groups, forming Si-OC covalent bonds and building an interpenetrating network (IPN). Titanate catalysis can accelerate the sol-gel transition and increase the crosslink density of the resin.

[0086] In some embodiments, the method for preparing the Al2O3@SiO2 core-shell particles comprises:

[0087] Hydroxylated Al2O3 is dispersed in a KH-550 ethanol solution and stirred at 60°C for 4 hours to allow silane to bond to the Al2O3 surface to obtain modified Al2O3; tetraethyl orthosilicate is added to the ethanol / water mixed solution of the modified Al2O3, and ammonia water is slowly added dropwise to adjust the pH value to 9-10. The solution is then stirred at a constant temperature of 50°C for 6 hours to allow the tetraethyl orthosilicate to hydrolyze to generate SiO2 and deposit on the Al2O3 surface, and a coating is obtained by centrifugation; the coating is calcined at a high temperature to obtain the Al2O3@SiO2 core-shell particles; the high-temperature calcination temperature is 550-650°C and the time is 1.5-2.5 hours.

[0088] During the preparation of Al2O3@SiO2 core-shell particles, a silane coupling agent bonds to the surface hydroxyl groups of Al2O3, improving the uniformity of the SiO2 coating. Calcination at a temperature of 550-650°C densifies the amorphous SiO2 shell, significantly enhancing its acid resistance and thermal shock resistance.

[0089] S2, mixing a polyimide-siloxane hyperbranched resin, a Zr-Ti-V composite oxide, and a nano-kaolinite / talc powder mixture to obtain the intermediate layer coating;

[0090] It should be noted that step S2 specifically comprises: placing a polyimide-siloxane hyperbranched resin in a mixing container and heating it to an appropriate temperature to soften it. Adding a Zr-Ti-V composite oxide and mixing it using a high-speed disperser to ensure that the oxide particles are evenly dispersed in the resin. Adding a nano-kaolinite / talc mixture and continuing to mix until the nanoparticles are fully contacted with the resin and coated.

[0091] In some embodiments, the method for preparing the polyimide-siloxane hyperbranched resin comprises:

[0092] A polyimide prepolymer, a hydroxyl-terminated polydimethylsiloxane, and a titanate catalyst are added to an organic solvent to carry out a condensation reaction at 120° C. for 8 hours to obtain a third mixed liquid; a vinyl siloxane side chain is added to the third mixed liquid, and the mixture is reacted at 80° C. for 4 hours to hydrolyze and condense the siloxane to form branching points to obtain a fourth mixed liquid; a benzocyclobutene crosslinker and a free radical initiator are added to the fourth mixed liquid, and the mixture is then heated to 140° C. and reacted under nitrogen for 6 hours to open the ring structure of the benzocyclobutene crosslinker and crosslink with the vinyl siloxane side chain to obtain a fifth mixed liquid; and the fifth mixed liquid is post-treated and purified to obtain the polyimide-siloxane hyperbranched resin.

[0093] During the preparation of polyimide-siloxane hyperbranched resins, the introduction of vinyl siloxane branches creates branching points through hydrolysis and condensation, balancing flexibility and temperature resistance. During crosslinking with benzocyclobutene, the tetrafunctional crosslinker ring-opens and grafts onto the vinyl branches, forming a three-dimensional hyperbranched network and raising the thermal decomposition temperature.

[0094] In some embodiments, the method for preparing the Zr-Ti-V oxide comprises:

[0095] A zirconium nitrate solution, a tetrabutyl titanate solution and an ammonium metavanadate solution are mixed, and ammonia water is slowly added dropwise to adjust the pH value to 8.8-9.2 to carry out a coprecipitation reaction to form a precipitate; the temperature of the coprecipitation reaction is room temperature and the time is 12-24 hours; the precipitate is calcined to obtain a Zr-Ti-V composite oxide sintered block; the calcination temperature is 1100-1300°C and the time is 3-5 hours; the Zr-Ti-V composite oxide sintered block is high-energy ball milled to obtain the Zr-Ti-V oxide.

[0096] In the preparation process of Zr-Ti-V oxide, the coprecipitation pH is 8.8-9.2, which can ensure that Zr 4+ 、Ti 4+ 、V 5+ Complete co-precipitation to avoid component segregation and form a uniform solid solution (ZrTiO4-VO x ). Bimodal particles can be obtained by high-energy ball milling.

[0097] S3. Mixing the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, silica aerogel and ammonium polyphosphate / zinc borate compound to obtain the surface coating.

[0098] It should be noted that the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin in the topcoat is the same as that in the basecoat to ensure resin quality. Step S3 is specifically as follows: Place the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin in a mixing container and heat it to an appropriate temperature. Slowly add the silica aerogel and use a low-speed stirrer to mix to avoid damage to the aerogel structure. Add the ammonium polyphosphate / zinc borate compound and continue mixing to ensure that the flame retardant is evenly dispersed in the resin.

[0099] This application uses a magnetic field to disperse boron nitride (BN) in a directional manner, aligning the BN sheets along the direction of heat flow (parallel to the coating surface), forming an axial high-thermal conductivity channel that quickly removes heat from local high-temperature areas (such as engine combustion chambers). The (002) crystal plane of BN has anisotropic thermal conductivity, and the magnetic field induces its crystal plane orientation, improving the in-plane thermal conductivity. By vertically spraying silica aerogel, the silica aerogel is sprayed layer by layer in the vertical direction to form a radial ultra-low thermal conductivity thermal insulation barrier, blocking heat transfer to the substrate.

[0100] In the third aspect, the present application provides a high-temperature resistant coating, which is formed by spraying and curing the powder coating with good high-temperature resistance described in any one of the first aspects. In the high-temperature resistant coating, the boron nitride is oriented along the direction of heat flow through the magnetic field, and forms an anisotropic thermal conductive-insulating network with the silica aerogel.

[0101] This application achieves a performance breakthrough in high-temperature resistant coatings through multi-scale structural design and precise interface control, and is suitable for high-end fields such as aerospace, nuclear power, and new energy vehicles.

[0102] In a fourth aspect, the present application provides a method for preparing the high-temperature resistant coating according to the third aspect, the method comprising:

[0103] The primer is sprayed onto the surface of the substrate, and a transverse magnetic field is applied parallel to the substrate surface to orient the boron nitride flakes along the direction of heat flow to form a bottom layer;

[0104] Spraying the intermediate layer coating onto the surface of the bottom layer to form an intermediate layer;

[0105] The surface coating is vertically sprayed onto the surface of the intermediate layer to form an axial heat conduction-radial heat insulation network, and then cured to obtain the high-temperature resistant coating.

[0106] In some embodiments, the transverse magnetic field has a magnetic field strength of ≥1 T and an action time of ≥30 min.

[0107] It should be noted that the magnetic field strength of the transverse magnetic field needs to be ≥1T (Tesla) and the action time needs to be ≥30min to overcome the diamagnetism of BN and the viscous resistance of the system and ensure that the layers are arranged along the direction of heat flow (such as parallel to the coating surface).

[0108] This application achieves comprehensive improvements in thermal management, mechanical strength, environmental tolerance, and safety of high-temperature resistant coatings through component synergy, structural design, and process innovation, providing an innovative solution for material protection in extreme environments. Specifically, it demonstrates the following core advantages:

[0109] (1) Excellent high temperature resistance: Through the synergistic effect of the rigid-flexible resin matrix and the high-temperature stable filler, the heat resistance limit and thermal stability of the coating are significantly improved, effectively inhibiting thermal oxidative decomposition and structural failure in high temperature environments, ensuring long-term reliability under extreme temperatures.

[0110] (2) Intelligent thermal management capability: Combining the dual design of directional heat conduction and gradient thermal insulation, it achieves the synergistic effect of rapid heat conduction and efficient heat insulation, protecting the substrate from thermal damage in high-temperature environments while optimizing the uniformity of heat distribution.

[0111] (3) Excellent mechanical properties and durability: The introduction of nano-reinforced fillers significantly improves the hardness, wear resistance and impact resistance of the coating. The interface optimization technology enhances the adhesion between the coating and the substrate, effectively extending the service life and resisting complex stress environments.

[0112] (4) Corrosion resistance and environmental tolerance: The design of core-shell structure filler and dense cross-linked network gives the coating excellent resistance to chemical corrosion, thermal shock and environmental erosion, adapting to the protection needs under harsh working conditions.

[0113] (5) Highly efficient flame retardancy and safety protection: The synergistic effect of the flame retardant system forms a dense protective layer, effectively inhibiting the spread of flames and reducing smoke release, improving the safety and environmental friendliness of the material, and meeting the protection standards for high-risk scenarios.

[0114] (6) Process-driven structural optimization: Innovative processes such as magnetic field oriented arrangement and gradient spraying ensure the precise distribution and microstructure control of functional fillers, maximize the material performance potential, and achieve customization of coating functions and structures.

[0115] (7) Wide applicability: It is suitable for high-end industrial fields such as aerospace engine thermal barrier coatings, nuclear power equipment protection, and new energy vehicle battery fire protection. It has the advantages of lightweight, long-term protection and adaptability to complex working conditions.

[0116] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.

[0117] Example 1

[0118] This embodiment provides a powder coating with good high temperature resistance, the powder coating is composed of a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0119] The primer is composed of the following chemical components: 30 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 10 parts of boron nitride, 4 parts of KH-550 modified silicon carbide, and 6 parts of Al2O3@SiO2 core-shell particles;

[0120] The intermediate layer coating is composed of the following chemical components: 15 parts of polyimide-siloxane hyperbranched resin, 4 parts of Zr-Ti-V composite oxide, and 2 parts of nano-kaolinite / talc powder mixture;

[0121] The surface coating is composed of the following chemical components: 16 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 11 parts of silica aerogel, and 2 parts of ammonium polyphosphate / zinc borate compound.

[0122] Wherein, in the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 2:1;

[0123] In the ammonium polyphosphate / zinc borate compound, the ratio of ammonium polyphosphate to zinc borate is 2.5:1;

[0124] The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm, and the mass ratio of the two is 1:1;

[0125] The organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials in parts by mass: 60 parts of polymethylphenylsiloxane, 25 parts of bisphenol A epoxy resin, and 15 parts of fluorine-terminated polyarylethersulfone;

[0126] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 50 parts of polyimide, 15 parts of benzocyclobutene crosslinking agent, 25 parts of hydroxyl-terminated polydimethylsiloxane, and 10 parts of vinyl siloxane side chain.

[0127] Based on the above powder coating, this embodiment also provides a method for preparing any one of the above powder coatings with good high temperature resistance, the method comprising:

[0128] S11, mixing a silicone-epoxy-polyarylethersulfone ternary hybrid resin, boron nitride, KH-550 modified silicon carbide and Al2O3@SiO2 core-shell particles to obtain the primer;

[0129] The preparation method of the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises: heating polyarylethersulfone (CAS No. 9002-88-4) to 120° C., adding trifluoromethylphenol (molar amount is 2% of the total amount of polyarylethersulfone monomer), continuing the reaction for 3 hours, connecting the fluorine group to the end of the polymer chain through a nucleophilic substitution reaction, cooling to room temperature, dripping the reaction solution into a deionized water / ethanol mixed solution to precipitate the polymer, filtering, washing to neutrality, and vacuum drying for 24 hours to obtain a fluorine-terminated polyarylethersulfone; and mixing polymethylphenylsiloxane (CAS No. 63148-58-3), bisphenol A type An epoxy resin (CAS number 25085-99-8) and a fluorine-terminated polyarylethersulfone are added to an N-methylpyrrolidone (NMP) solvent (mass ratio 1:2) to obtain a first mixed solution; the pH value of the first mixed solution is adjusted to 3.5, and the mixture is stirred and reacted at 60° C. for 6 hours to form a sol-gel interpenetrating network to obtain a second mixed solution; a titanate catalyst (CAS number 5593-70-4, the mass of the titanate catalyst being 1% of the total mass of the second mixed solution) is added to the second mixed solution, and the mixture is heated to 120° C. and reacted for 2 hours to obtain the silicone-epoxy-polyarylethersulfone ternary hybrid resin.

[0130] The preparation method of KH-550-modified silicon carbide includes: immersing SiC powder (CAS number 409-21-2) in dilute hydrochloric acid and ultrasonically treating for 30 minutes to remove surface metal oxides and impurities; repeatedly washing with deionized water until the filtrate has a pH of ≈7; and vacuum drying at 100°C for 6 hours to obtain activated SiC. KH-550 is dissolved in an ethanol / water mixture at a mass ratio of 3% (relative to SiC) and the pH is adjusted to 4-5 with acetic acid; stirring is performed at room temperature for 30 minutes to fully hydrolyze the KH-550 to form silanols (Si-OH). The activated SiC is added to the hydrolyzed KH-550 solution and stirred at 70°C for 3 hours; the silanols condense with the hydroxyl groups (-OH) on the SiC surface to form Si-O-Si covalent bonds, thereby grafting amino groups (-NH2) onto the surface. The modified SiC was collected by centrifugation at 4000 rpm for 10 minutes; the unreacted KH-550 was removed by washing with anhydrous ethanol for 3 times to obtain KH-550-modified silicon carbide.

[0131] The preparation method of the Al2O3@SiO2 core-shell particles includes: dispersing hydroxylated Al2O3 in a KH-550 ethanol solution, stirring at 60°C for 4 hours to allow silane to bond to the Al2O3 surface, thereby obtaining modified Al2O3; adding tetraethyl orthosilicate to the ethanol / water mixed solution of the modified Al2O3, slowly adding ammonia water to adjust the pH value to 9.5, and then stirring at a constant temperature of 50°C for 6 hours to allow the tetraethyl orthosilicate to hydrolyze to generate SiO2 and deposit on the Al2O3 surface, and centrifuging to obtain a coating; and calcining the coating at high temperature to obtain the Al2O3@SiO2 core-shell particles; the high-temperature calcination temperature is 600°C and the time is 2 hours.

[0132] S21, mixing a polyimide-siloxane hyperbranched resin, a Zr-Ti-V composite oxide, and a nano-kaolinite / talc powder mixture to obtain the intermediate layer coating;

[0133] The preparation method of the polyimide-siloxane hyperbranched resin comprises: mixing octamethylcyclotetrasiloxane and concentrated sulfuric acid (0.7 wt %) in toluene, heating to 90° C. under nitrogen protection, stirring and reacting for 5 hours, cooling to 50° C., slowly adding deionized water (2.5 times the molar amount of octamethylcyclotetrasiloxane), continuing the reaction for 1 hour, hydrolyzing the terminal silicon-oxygen bond (Si-O-Si) to generate a hydroxyl group (-OH), washing with a NaHCO3 solution, separating the liquid to remove the aqueous phase, and removing the solvent by reduced pressure distillation to obtain a hydroxyl-terminated polydimethylsiloxane; polycondensing biphenyltetracarboxylic dianhydride (BPDA) and 4,4'-diaminodiphenyl ether (ODA) in NMP (80° C., 6 hours) to generate a polyamic acid prepolymer; and mixing the polyimide prepolymer, the hydroxyl-terminated polydimethylsiloxane and titanium. An acid ester catalyst is added to dimethyl sulfoxide to carry out a condensation reaction at 120° C. for 8 hours to obtain a third mixed solution; a vinyl siloxane side chain (vinyltrimethoxysilane, CAS No. 2768-02-7) is added to the third mixed solution, and the mixture is reacted at 80° C. for 4 hours to hydrolyze and condense the siloxane to form branching points, thereby obtaining a fourth mixed solution; a benzocyclobutene crosslinker (CAS No. 694-87-1) and a free radical initiator (diisopropylbenzene peroxide) are added to the fourth mixed solution, and the mixture is heated to 140° C. and reacted under nitrogen for 6 hours to open the ring structure of the benzocyclobutene crosslinker and crosslink with the vinyl siloxane side chain to obtain a fifth mixed solution; and the fifth mixed solution is post-treated and purified to obtain the polyimide-siloxane hyperbranched resin.

[0134] The preparation method of the Zr-Ti-V oxide includes: mixing a zirconium nitrate solution, a tetrabutyl titanate solution and an ammonium metavanadate solution, and slowly adding ammonia water to adjust the pH value to 9.0 to perform a co-precipitation reaction to form a precipitate; the temperature of the co-precipitation reaction is room temperature and the time is 20 hours; calcining the precipitate to obtain a Zr-Ti-V composite oxide sintered block; the calcination temperature is 1200°C and the time is 4 hours; and high-energy ball milling the Zr-Ti-V composite oxide sintered block to obtain the Zr-Ti-V oxide.

[0135] The preparation method of the nano-kaolinite / talc powder composite comprises: drying the nano-kaolinite and talc powder at 150° C. for 2 hours to remove adsorbed moisture; surface treating the kaolinite / talc powder with a silane coupling agent KH-550 to improve compatibility with the resin; adding the dried kaolinite and talc powder in proportion to a high-speed mixer, mixing at a speed of 1000 rpm for 60 minutes to ensure uniform dispersion; and filtering through a 200-mesh sieve to remove agglomerated particles to obtain the nano-kaolinite / talc powder composite.

[0136] S31. Mixing a silicone-epoxy-polyarylethersulfone ternary hybrid resin, silica aerogel (Forsman brand aerogel powder, CAS No. 102262-30-6) and an ammonium polyphosphate / zinc borate compound to obtain the surface coating.

[0137] The preparation method of the ammonium polyphosphate / zinc borate compound comprises: drying ammonium polyphosphate (CAS number 68333-79-9) and zinc borate at 80°C for 4 hours to prevent moisture absorption and agglomeration; adding APP and ZB in proportion into a high-speed mixer, mixing at a speed of 500 rpm for 30 minutes to ensure uniform dispersion, passing through a 100-mesh sieve, and sealing and storing in a dry environment to obtain the ammonium polyphosphate / zinc borate compound.

[0138] Based on the above-mentioned powder coating, this embodiment also provides a high-temperature resistant coating, which is formed by spraying and curing the above-mentioned powder coating. In the high-temperature resistant coating, the boron nitride is oriented along the direction of heat flow through a magnetic field and forms an anisotropic thermal conductive-insulating network with the silica aerogel.

[0139] Based on the above-mentioned high-temperature resistant coating, this embodiment also provides a method for preparing the high-temperature resistant coating, comprising the following steps:

[0140] The basecoat was sprayed onto the surface of the substrate, and a transverse magnetic field was applied parallel to the substrate surface to align the boron nitride flakes along the heat flow direction, forming a basecoat. The coating was applied electrostatically (70 kV, 0.5 MPa, spray distance 25 cm) to a thickness of 80 μm. A 1.2 T transverse magnetic field (parallel to the substrate) was maintained for 30 minutes. The intermediate layer was sprayed onto the surface of the basecoat to form an intermediate layer. The coating was applied electrostatically without a magnetic field to a thickness of 50 μm. After spraying, the temperature was increased to 150°C at 3°C / min and pre-cured for 1 hour to release interlaminar stress. The topcoat was sprayed perpendicularly onto the surface of the intermediate layer to form an axial heat conduction-radial insulation network. The topcoat was sprayed vertically at low pressure (0.3 MPa, nozzle 0.4 mm) to a thickness of 50 μm, forming a radial insulation barrier. Pre-curing was performed at 80°C for 1 hour to fix the BN oriented structure. The temperature was then increased to 180°C at 5°C / min and held for 2 hours to fully crosslink the ternary hybrid resin. Then, under Ar gas protection, the temperature was raised to 320°C at 3°C / min and kept at that temperature for 1 hour to activate the heat resistance of the polyimide segments. The temperature was then lowered to room temperature at ≤2°C / min to reduce the risk of thermal stress cracking, thereby obtaining the high-temperature resistant coating.

[0141] Example 2

[0142] This embodiment is modified as follows based on the disclosure of embodiment 1:

[0143] This embodiment provides a powder coating with good high temperature resistance, the powder coating is composed of a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0144] The primer is composed of the following chemical components: 38 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5 parts of boron nitride, 6 parts of KH-550 modified silicon carbide, and 3 parts of Al2O3@SiO2 core-shell particles;

[0145] The intermediate layer coating is composed of the following chemical components: 18 parts of polyimide-siloxane hyperbranched resin, 3 parts of Zr-Ti-V composite oxide, and 1 part of nano-kaolinite / talc powder mixture;

[0146] The surface coating is composed of the following chemical components: 10 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 15 parts of silica aerogel, and 1 part of ammonium polyphosphate / zinc borate compound.

[0147] Wherein, in the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 3:1;

[0148] In the ammonium polyphosphate / zinc borate compound, the ratio of ammonium polyphosphate to zinc borate is 3:1;

[0149] The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm, with a mass ratio of 1:2.

[0150] The organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials, in parts by mass: 65 parts of polymethylphenylsiloxane, 20 parts of bisphenol A epoxy resin, and 15 parts of fluorine-terminated polyarylethersulfone;

[0151] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: polyimide: 55 parts, benzocyclobutene crosslinking agent: 20 parts, terminal hydroxyl polydimethylsiloxane: 20 parts, and vinyl siloxane side chain: 5 parts.

[0152] Example 3

[0153] This embodiment is modified as follows based on the disclosure of embodiment 1:

[0154] This embodiment provides a powder coating with good high temperature resistance, the powder coating is composed of a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0155] The primer is composed of the following chemical components: 20 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 14 parts of boron nitride, 2 parts of KH-550 modified silicon carbide, and 8 parts of Al2O3@SiO2 core-shell particles;

[0156] The intermediate layer coating is composed of the following chemical components: 20 parts of polyimide-siloxane hyperbranched resin, 6 parts of Zr-Ti-V composite oxide, and 4 parts of nano-kaolinite / talc powder mixture;

[0157] The surface coating is composed of the following chemical components: 18 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5 parts of silicon dioxide aerogel, and 3 parts of ammonium polyphosphate / zinc borate compound.

[0158] Wherein, in the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 1:1;

[0159] In the ammonium polyphosphate / zinc borate compound, the ratio of ammonium polyphosphate to zinc borate is 2:1;

[0160] The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm, with a mass ratio of 2:1.

[0161] The organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials in parts by mass: 50 parts of polymethylphenylsiloxane, 30 parts of bisphenol A epoxy resin, and 20 parts of fluorine-terminated polyarylethersulfone;

[0162] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 50 parts of polyimide, 20 parts of benzocyclobutene crosslinking agent, 20 parts of hydroxyl-terminated polydimethylsiloxane, and 10 parts of vinyl siloxane side chain.

[0163] Example 4

[0164] This embodiment is modified as follows based on the disclosure of embodiment 1:

[0165] This embodiment provides a powder coating with good high temperature resistance, the powder coating is composed of a base coating, an intermediate coating and a top coating; wherein, in parts by mass,

[0166] The primer is composed of the following chemical components: 32 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 12 parts of boron nitride, 5 parts of KH-550 modified silicon carbide, and 4 parts of Al2O3@SiO2 core-shell particles;

[0167] The intermediate layer coating is composed of the following chemical components: 20 parts of polyimide-siloxane hyperbranched resin, 4 parts of Zr-Ti-V composite oxide, and 2 parts of nano-kaolinite / talc powder mixture;

[0168] The surface coating is composed of the following chemical components: 12 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 8 parts of silicon dioxide aerogel, and 1 part of ammonium polyphosphate / zinc borate compound.

[0169] Wherein, in the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 1:1;

[0170] In the ammonium polyphosphate / zinc borate compound, the ratio of ammonium polyphosphate to zinc borate is 3:1;

[0171] The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm, and the mass ratio of the two is 1:1;

[0172] The organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials in parts by mass: 60 parts of polymethylphenylsiloxane, 22 parts of bisphenol A epoxy resin, and 18 parts of fluorine-terminated polyarylethersulfone;

[0173] The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 55 parts of polyimide, 15 parts of benzocyclobutene crosslinking agent, 25 parts of hydroxyl-terminated polydimethylsiloxane, and 5 parts of vinyl siloxane side chain.

[0174] Comparative Example 1

[0175] This comparative example is modified as follows based on Example 1:

[0176] Powder coating consists of an intermediate coating and a topcoat, that is, it lacks a primer.

[0177] Comparative Example 2

[0178] This comparative example is modified as follows based on Example 1:

[0179] Powder coating consists of a base coat and a top coat, that is, there is no intermediate coat.

[0180] Comparative Example 3

[0181] This comparative example is modified as follows based on Example 1:

[0182] Powder coating consists of a base coat and an intermediate coat, that is, it lacks a top coat.

[0183] Comparative Example 4

[0184] This comparative example is modified as follows based on Example 1:

[0185] The primer is composed of the following chemical components: 32 parts of organosilicon-epoxy binary hybrid resin, 12 parts of boron nitride, 5 parts of KH-550 modified silicon carbide, and Al2O3@SiO2 core-shell particles.

[0186] Comparative Example 5

[0187] This comparative example is modified as follows based on Example 1:

[0188] No boron nitride was added to the primer.

[0189] Comparative Example 6

[0190] This comparative example is modified as follows based on Example 1:

[0191] No Al2O3@SiO2 core-shell particles are added to the primer.

[0192] Comparative Example 7

[0193] This comparative example is modified as follows based on Example 1:

[0194] No Zr-Ti-V composite oxide is added to the intermediate layer coating.

[0195] Comparative Example 8

[0196] This comparative example is modified as follows based on Example 1:

[0197] No silica aerogel is added to the topcoat.

[0198] The performance of the high temperature resistant coatings obtained in Examples 1 to 4 and Comparative Examples 1 to 8 was measured. The specific measurement methods are shown in Table 1, and the performance results are shown in Tables 2 and 3.

[0199] Table 1 Performance determination method of high temperature resistant coating

[0200]

[0201] Table 2 Performance of high temperature resistant coatings of Examples 1 to 4

[0202]

[0203]

[0204] As shown in Table 2, the high temperature resistant coatings obtained in Examples 1 to 4 have an axial thermal conductivity of 45 to 55 W / (m·K) due to the directional arrangement of the bottom BN + the rigid skeleton of the ternary hybrid resin; the radial thermal conductivity is 0.025 to 0.035 W / (m·K) due to the heat insulation of the surface aerogel pores + the dispersion of the nanofiller in the middle layer; the adhesion is 3B to 4B (cross-hatch method) due to the high adhesion of the bottom resin + the interfacial bonding of the hyperbranched resin in the middle layer; the "hard-soft" composite of the bottom KH-550 modified silicon carbide + Al2O3@SiO2 core-shell particles , wear resistance is 3 to 8 mg loss (Taber abrasion); due to the surface layer APP / ZB compound + the intermediate layer Zr-Ti-V oxide catalytic carbonization, the flame retardancy is UL-94V-0 to V-1 level, LOI35 to 42%; due to the stress buffering of the intermediate layer nano-kaolinite / talc powder + the plastic deformation of the bottom layer core-shell particles, the thermal shock resistance is 6 to 10 cycles without cracking; due to the phase change toughening of the intermediate layer Zr-Ti-V + the decomposition and absorption of heat by the hyperbranched resin siloxane, the high-temperature oxidation stability is a weight loss of 0.3 to 1.2% at 1000℃ / 10h.

[0205] Table 3 Performance of high temperature resistant coatings of Comparative Examples 1 to 8

[0206]

[0207]

[0208] As shown in Table 3, Comparative Example 1 lacks a base layer, and its absence leads to a decrease in axial thermal conductivity (missing the BN directional thermal network). The base layer serves as the bonding layer between the substrate and the coating, and its absence reduces adhesion. Without a base layer to buffer thermal stress, the film cracked after only two cycles.

[0209] Comparative Example 2 lacks an intermediate layer, which results in a mismatch in thermal expansion coefficients and cracking after five thermal shock cycles. The synergistic flame retardancy between the intermediate layer of Zr-Ti-V oxide and APP / ZB is missing, resulting in a lower LOI.

[0210] In Comparative Example 3, there is no surface layer, and the absence of aerogel leads to an increase in radial thermal conductivity. The absence of APP / ZB in the surface layer reduces LOI.

[0211] Comparative Example 4 uses a binary resin, and the ternary hybrid resin is changed to a binary resin (without PAES). The high-temperature rigidity is insufficient and the wear resistance is reduced. The lack of the aromatic ring structure of PAES leads to an increase in oxidation weight loss.

[0212] Comparative Example 5 contains no BN. The lack of BN results in a decrease in axial thermal conductivity. The wear resistance of the BN layered structure is lost, resulting in increased wear.

[0213] Comparative Example 6 lacks core-shell particles. The lack of Al2O3@SiO2 leads to a decrease in thermal stress buffering capacity and cracking after six thermal shock cycles. The SiO2 shell is missing, which reduces corrosion resistance.

[0214] Comparative Example 7 lacks Zr-Ti-V, resulting in a loss of toughness due to phase transformation, increased oxidation weight loss, and a failure in the synergistic flame retardancy of Zr-Ti-V and APP, resulting in a decreased LOI.

[0215] In Comparative Example 8, which lacks aerogel, the radial thermal conductivity increases, resulting in a significant rise in substrate temperature. The oxygen barrier effect of the aerogel pores is lost, resulting in a lower LOI.

[0216] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a hard limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numbers within the range. For example, the description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0217] In addition, in the description of the specification of this application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" refers to one or more, and "plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass represent the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0218] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A powder coating with good high temperature resistance, characterized in that: The powder coating consists of a base coating, an intermediate coating and a top coating; wherein, in parts by mass, The primer is composed of the following chemical components: 20-40 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of boron nitride, 2-6 parts of KH-550 modified silicon carbide, and 3-8 parts of Al2O3@SiO2 core-shell particles; The intermediate layer coating is composed of the following chemical components: 10-20 parts of polyimide-siloxane hyperbranched resin, 3-6 parts of Zr-Ti-V composite oxide, and 1-4 parts of nano-kaolinite / talc powder mixture; The surface coating consists of the following chemical components: 10-20 parts of organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, 5-15 parts of silicon dioxide aerogel, and 1-3 parts of ammonium polyphosphate / zinc borate compound.

2. The powder coating with excellent high temperature resistance according to claim 1, characterized in that: In the nano-kaolinite / talc powder compound, the mass ratio of nano-kaolinite to talc powder is 1:1 to 3:1; In the ammonium polyphosphate / zinc borate compound, the mass ratio of ammonium polyphosphate to zinc borate is 2:1 to 3:1; The Zr-Ti-V composite oxide is a bimodal nanoparticle composed of large particles of 50 to 100 nm and small particles of 5 to 20 nm.

3. The powder coating with excellent high temperature resistance according to claim 1, characterized in that: The organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises the following raw materials, in parts by mass: 50-65 parts of polymethylphenylsiloxane, 20-30 parts of bisphenol A epoxy resin, and 10-20 parts of fluorine-terminated polyarylethersulfone; The polyimide-siloxane hyperbranched resin comprises the following raw materials in parts by mass: 50 to 80 parts of polyimide prepolymer, 12 to 20 parts of benzocyclobutene crosslinking agent, 20 to 35 parts of hydroxyl-terminated polydimethylsiloxane, and 5 to 15 parts of vinyl siloxane side chains.

4. A method for preparing a powder coating with good high temperature resistance, for preparing the powder coating with good high temperature resistance according to any one of claims 1 to 3, characterized in that: The method comprises: Mixing organosilicon-epoxy-polyarylethersulfone ternary hybrid resin, boron nitride, KH-550 modified silicon carbide and Al2O3@SiO2 core-shell particles to obtain the primer; Mixing a polyimide-siloxane hyperbranched resin, a Zr-Ti-V composite oxide, and a nano-kaolinite / talc powder mixture to obtain the intermediate layer coating; The surface coating is obtained by mixing a ternary hybrid resin of organosilicon-epoxy-polyarylethersulfone, a silica aerogel and an ammonium polyphosphate / zinc borate compound.

5. The method for preparing a powder coating having excellent high temperature resistance according to claim 4, characterized in that: The preparation method of the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin comprises: Adding polymethylphenylsiloxane, bisphenol A epoxy resin and fluorine-terminated polyarylethersulfone to an organic solvent in proportion to obtain a first mixed solution; Adjusting the pH value of the first mixed solution to 3-4 and performing a stirring reaction to form a sol-gel interpenetrating network to obtain a second mixed solution; A titanate catalyst was added to the second mixed liquid, and the temperature was raised to 120° C. for reaction for 2 hours to obtain the organosilicon-epoxy-polyarylethersulfone ternary hybrid resin.

6. The method for preparing a powder coating having excellent high temperature resistance according to claim 4, wherein: The preparation method of the polyimide-siloxane hyperbranched resin comprises: adding a polyimide prepolymer, a hydroxyl-terminated polydimethylsiloxane, and a titanate catalyst into an organic solvent to carry out a condensation reaction at 120° C. for 8 hours to obtain a third mixed solution; Adding vinyl siloxane side chains to the third mixed solution and reacting at 80° C. for 4 hours to hydrolyze and condense the siloxane to form branching points, thereby obtaining a fourth mixed solution; Adding a benzocyclobutene crosslinker and a free radical initiator to the fourth mixed solution, then heating to 140° C. and reacting for 6 hours under nitrogen protection to open the ring structure of the benzocyclobutene crosslinker and crosslink the vinylsiloxane side chains, to obtain a fifth mixed solution; The fifth mixed liquid is post-processed and purified to obtain the polyimide-siloxane hyperbranched resin.

7. The method for preparing a powder coating having excellent high temperature resistance according to claim 4, characterized in that: The preparation method of the Zr-Ti-V oxide comprises: The zirconium nitrate solution, tetrabutyl titanate solution and ammonium metavanadate solution are mixed, and ammonia water is slowly added dropwise to adjust the pH value to 8.8-9.2 to perform a coprecipitation reaction to form a precipitate; the coprecipitation reaction temperature is room temperature and the time is 12-24 hours; calcining the precipitate to obtain a Zr-Ti-V composite oxide sintered block; the calcination temperature is 1100-1300° C., and the time is 3-5 hours; The Zr-Ti-V composite oxide sintered block is subjected to high-energy ball milling to obtain the Zr-Ti-V oxide.

8. The method for preparing a powder coating having excellent high temperature resistance according to claim 4, wherein: The preparation method of the Al2O3@SiO2 core-shell particles comprises: The hydroxylated Al2O3 was dispersed in KH-550 ethanol solution and stirred at 60°C for 4 hours to allow the silane to bond to the Al2O3 surface to obtain modified Al2O3; Adding ethyl orthosilicate to an ethanol / water mixed solution of modified Al2O3, and slowly adding ammonia water to adjust the pH value to 9-10, then stirring at a constant temperature of 50°C for 6 hours to allow the ethyl orthosilicate to hydrolyze to generate SiO2 and deposit on the Al2O3 surface, and centrifuging to obtain a coating; The coating is calcined at high temperature to obtain the Al2O3@SiO2 core-shell particles; the temperature of the high temperature calcination is 550-650°C and the time is 1.5-2.5h.

9. A high temperature resistant coating, characterized in that: The high-temperature resistant coating is formed by spraying and curing the powder coating with good high-temperature resistance as described in any one of claims 1 to 3. In the high-temperature resistant coating, the boron nitride is oriented along the direction of heat flow through a magnetic field and forms an anisotropic thermal conductive-insulating network with the silica aerogel.

10. A method for preparing a high temperature resistant coating, for preparing the high temperature resistant coating according to claim 9, characterized in that: The method comprises: The primer is sprayed onto the surface of the substrate, and a transverse magnetic field is applied parallel to the substrate surface to orient the boron nitride flakes along the direction of heat flow to form a bottom layer; Spraying the intermediate layer coating onto the surface of the bottom layer to form an intermediate layer; The surface coating is vertically sprayed onto the surface of the intermediate layer to form an axial heat conduction-radial heat insulation network, and then cured to obtain the high-temperature resistant coating.

Citation Information

Patent Citations

  • Boron-modified organic silicon resin zinc-aluminum composite coating and preparation method thereof

    CN104650731A

  • Insulating weather-resistant powder coating and preparation method thereof

    CN119931500A

  • Heat-conducting wave-absorbing auxiliary agent, low-temperature curing coating, heavy corrosion-resistant coating, and preparation method therefor and use thereof

    WO2024149031A1

Cited By

  • Gradient temperature-resistant coating system and application method thereof

    CN121046839A